LATENCY OF RESPONSE DURING THE FUNCTIONAL ANALYSIS OF ELOPEMENT. Issue 1 (20th February 2013) - Neidert, Pamela L.; Iwata, Brian A.; Dempsey, Carrie M.; Thomason‐Sassi, Jessica L.
Abstract Elopement is a dangerous behavior sometimes exhibited by individuals with intellectual disabilities. We conducted trial‐based functional analyses in which latency was the index of elopement for 2 students. Two unobtrusive safety monitors were placed outside the building to eliminate potential confounding caused by having to retrieve a student. Results of both students' assessments indicated that elopement served multiple functions. Results are discussed in terms of the study's methodological and applied implications.